PENGARUH PEMBERIAN KOMPOS SERASAH KACANG TANAH DAN NPK 16.16.16 TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Siregar, Khusnu Abdillah; Bahar, Edward; Irawan, Yuli (Universitas Pasir Pengaraian, 2024)
Khusnu Abdillah Siregar, Effect of Peanut Litter Compost and NPK 16:16:16: on the Growth and Production of Shallots (Allium ascalonicum L.). This research will be carried out at the Screen House of the Faculty of Agriculture, University of Pasir Pengaraian, Jl Tuanku Tambusai, Rambah, Rambah Hilir, Rokan Hulu Regency, Riau. The time of this research will be carried out for four months starting from April to June 2023. The purpose of this study is to determine the interaction effect and the main influence on the growth and production of shallots given peanut litter compost and NPK Fertilizer 16:16:16 . This study used a completely randomized factorial design which consisted of two factors. The first factor was the dose of peanut litter compost (K) consisting of 4 levels and the second factor was the dose of NPK 16.16.16 (N) consisting of 4 levels so that 16 treatment combinations were obtained with 3 replications, so there were 48 experimental units. Each experimental unit (plot) consisted of 6 plants and 3 plants were used as research observation samples so that the total experimental unit was 266 plants. The results of the study concluded that the interaction of peanut litter compost and NPK 16:16:16 fertilizer had a significant effect on harvesting age, number of tubers per clump, fresh weight of tubers per clump, dry weight of tubers per clump and tuber weight loss. The best treatment was a combination of 45 g peanut litter compost per polybag and 112.5 g NPK 16:16:16 fertilizer per polybag (K3N3). The main effect of peanut litter compost is significant on all observation parameters. The best treatment was a dose of 45 g of peanut litter compost per polybag (K3). The main effect of the dose of NPK 16:16:16 fertilizer was significant for all observed parameters. The best treatment was the dose of NPK 16:16:16 112.5 g per polybag (N3).